Intermittent high glucose-induced oxidative stress modulates retinal pigmented epithelial cell autophagy and promotes cell survival via increased HMGB1 - Wei Zhang; Jian Song; Yue Zhang; Yingxue Ma; Jing Yang; Guanghui He; Song Chen (BMC Ophthalmology, 2018)
Abstract Background In this study, we evaluated the effects of intermittent high glucose on oxidative stress production in retinal pigmented epithelial (RPE) cells and explored whether the mechanisms of autophagy and apoptosis in oxidative stress are associated with high-mobility group box 1 (HMGB1) protein. Methods Cultured human RPE cell line ARPE-19 cells were exposed to intermittent high glucose-induced oxidative stress. Reactive oxygen species (ROS) was determined by 2′, 7′-dichlorofluorescin diacetate (DCFH-DA); and malonyldialdehyde (MDA), superoxide dismutase (SOD) by commercial kits. Transmission electron microscopy was used to observe the generation of autophagosome. And MTT assay was used to examine the effect of autophagy on cell viability. For the inhibition experiments, cells were pre-incubated with lysosomal inhibitors NH4Cl or N-acetyl cysteine (NAC).Western blot was used to measure the expression patterns of autophagic markers, including LC3 and p62. The expression of HMGB1 was detected by immunohistochemistry.Cells were pre-incubated with HMGB1 inhibitor ethyl pyruvate (EP) ,then detected the expression pattern of autophagic markers and level of cellular ROS. Results We found that intermittent high glucose significantly increased oxidative stress levels (as indicated by ROS, MDA, SOD), increased in the generation of autophagosome, decreased the level of p62, induced conversion of LC3 I to LC3 II. We further demonstrated that the NH4Cl/NAC inhibited intermittent high glucose-induced autophage by altered level of LC3 and p62. Intermittent high glucose-induced autophagy is independent of HMGB1 signaling, inhibition of HMGB1 release by EP decreased expression pattern of autophagic markers and level of cellular viability. Conclusions Under intermittent high glucose condition, autophagy may be required for preventing oxidative stress-induced injury in RPE. HMGB1 plays important roles in signaling for both autophagy and oxidative stress.